TAFSĪR AL-MUNĪR SEBAGAI TEKS HIPOGRAM TAFSIR AL-BAYĀN FĪ MA’RIFATI MA’ĀNI AL-QUR`ĀN: KAJIAN INTERTEKSTUAL - Sakinah, Fatihatus; Khasanah, Maulidah (UIN Raden Mas Said Surakarta, 2024)
This research is motivated by the tafsir Al-Munīr which is one of the tafsir books that is the majority of references for the tafsir al-Bayān. This study is important as a response to the work of Indonesian tafsir and as part of the academic contribution to studying it. This study uses a descriptive-analytical method by analyzing the intertext in the tafsir Al-Munīr as a hypogram of the tafsir Al-Bayān, with the focus of the study on QS. Al-Baqarah: 3-10. The results of this study indicate that there are two elements found, namely intrinsic (inner) and extrinsic (outer) elements. Intrinsic elements, in the interpretation of al-Bayān and Al-Munīr are the themes of believers, infidels, and hypocrites. Intrinsic differences include characters, settings and plots. Extrinsic elements in the interpretation of Al-Munīr and al-Bayān are the same to provide explanations of the verses of the Qur'an to readers. There are 2 forms of intertext in the form of transformation (translating, copying, diverting), and haplology (reduction). Al-Bayān with Javanese language ngoko Latin script provides a simple, concise, not long-winded description in accordance with the target of this interpretation being taught.